Prioritization of Urea Fertilizer 4Ps Marketing Mix: A Case Study - Hana Fathia Izazi; Bustanul Airifin Noer (Institut Teknologi Sepuluh Nopember, 2020)
Marketing strategy has its own important roles in increasing sales. By formulating the right marketing strategy, a company can increase its sales significantly. 4Ps marketing mix is a tool, consist of Product, Price, Promotion, and Place, that widely used to formulate marketing strategy. It will be beneficial for a company if they know which P is the most important, so they can formulate specific marketing strategies and allocate their resources effectively. This study aims to find the important weight of each P in the 4Ps marketing mix used in the retail sales of urea fertilizer by PT. X using the Analytic Hierarchy Process. AHP is a method used by many decision-makers to solve Multi-Criteria Decision Making (MCDM) problems. Because of its simplicity and flexibility, AHP is frequently used to solve other problems. The General Manager and Manager of Marketing of the company are asked to give their judgment on the pairwise comparisons between each P of the 4Ps marketing mix, considering their impacts on sales. The result shows that Place has the highest important weight. Price is more important than Product, and Promotion is the least important. The study suggested the company to broaden its network, by adding more kiosks.